BERBAGAI PENDEKATAN HERMENEUTIKA DALAM STUDI ISLAM: SEBUAH STUDI LITERATUR [VARIOUS APPROACHES TO HERMENEUTICS IN ISLAMIC STUDIES: A STUDY OF LITERATURE] - Suwardi, S; Syaifullah, Muhammad (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
Along with the development of the times and science, there is also a method of interpretation derived from philosophy, namely hermeneutics. Hermeneutics as a new method in the interpretation of the Qur'an is expected to be able to reveal things that cannot be known through the old method of interpretation. This study aims to examine the various hermeneutical approaches in Islamic studies. The method used in this research is literature study. The results of this study conclude that hermeneutics can be interpreted as an interpretation method that pays attention to the context of words (from a text) and the cultural context of their thoughts. Hermeneutics is divided into three varieties, namely the theory of hermeneutics which focuses its discussion on methodology, philosophy of hermeneutics whose focus is on tracing the ontological status of efforts to understand (understanding), and critical hermeneutics which emphasizes its language concerning efforts to uncover the causes of distortions in understanding. The hermeneutic method is considered to have a characteristic, namely the development of the contextualization value of a text to be studied. Hermeneutics in Islamic studies through the interpretation of the Qur’an finds a match between the verses of the Qur’an and science, which also shows the miracles of the Qur’an and its glory.